NON INVASIVE IMAGE CONTRAST ENHANCEMENT TECHNIQUE FOR RETINAL FUNDUS IMAGES - SOOMRO, TOUFIQUE AHMED (2014)
The analysis of retinal vasculature in digital fundus images is important for diagnosing eye related diseases in particular, diabetic retinopathy (DR). However, digital colour fundus images suffer from low and varied contrast. With added presence of noise it becomes difficult to analyse retinal vasculature digitally requiring the use of fundus angiogram modality. The fundus fluorescein angiogram (FFA) modality gives 5 to 6 time's higher contrast for the retinal vasculature but it is an invasive method (injection of contrasting dyes) that can lead to other physiological problems.—A reported digital image enhancement technique named RETICA thai combines Retinex and ICA techniques, reduces varied contrast, and enhances the low contrast blood vessels of model fundus images.